The Effects of Endurance Running Training on Young Adult Bone: Densitometry vs. Biomaterial Properties - Huang, Tsang-Hai; Chang, Ming-Yao; Chen, Kung-Tung; Hsieh, Sandy S.; Yang, Rong-Sen (IntechOpen, 2011)
None